2018
DOI: 10.1111/faam.12157
|View full text |Cite
|
Sign up to set email alerts
|

Publication outlets for healthcare financial research: A study of journal quality perceptions

Abstract: Publications in high quality journals often serve to indicate research productivity. However, many top‐rated journals infrequently publish cross‐disciplinary topics such as healthcare financial management (HFM). So, academic administrators and HFM researchers find it challenging to evaluate the quality of the work. Journals open to publishing HFM articles are distributed across multiple disciplines. Each field has its own journal rankings typically focused on their primary subject area. Starting with prior lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on the tables in Mercado et al (2022), information on publications of behavioral studies reported in Chapter 19, and the journal rankings by the Australian Business Deans Council (ABDC) for 2021, there are 14 journals that published ten or more nonprofit accounting articles in the 2000-2020 timeframe. These include: Additionally, Forgione, Liu, Smith, and Liu (2018) identify a number of outlets in the US and internationally for nonprofit accounting research dealing specifically with healthcare topics. Their Table 8 provides a cross-disciplinary list of 46 journals that a broad sample of authors, reviewers, and editors regard as high quality and open to healthcare management topics (including accounting).…”
Section: Statistics On the Growth In Nonprofit Researchmentioning
confidence: 99%
“…Based on the tables in Mercado et al (2022), information on publications of behavioral studies reported in Chapter 19, and the journal rankings by the Australian Business Deans Council (ABDC) for 2021, there are 14 journals that published ten or more nonprofit accounting articles in the 2000-2020 timeframe. These include: Additionally, Forgione, Liu, Smith, and Liu (2018) identify a number of outlets in the US and internationally for nonprofit accounting research dealing specifically with healthcare topics. Their Table 8 provides a cross-disciplinary list of 46 journals that a broad sample of authors, reviewers, and editors regard as high quality and open to healthcare management topics (including accounting).…”
Section: Statistics On the Growth In Nonprofit Researchmentioning
confidence: 99%